Vascular Anatomy and Clinical Application of the Free Proximal Ulnar Artery Perforator Flaps - Wei, Yitao (Plast Reconstr Surg Glob Open, 2014)
BACKGROUND: There is a dearth of detailed published work on the anatomy of ulnar artery perforators. The objective of this study was to fully document the vascular basis of the free proximal ulnar artery perforator flap and report its use in reconstruction of the hand. METHODS: (1) The ulnar artery perforators were studied in 25 fresh cadavers and 10 cast preparations. Cadavers were injected with lead oxide for 3-dimensional reconstruction. The origin, course, and distribution of the ulnar artery perforators were comprehensively documented. (2) Between August 2011 and January 2013, 29 free proximal ulnar artery perforator flaps were utilized for reconstruction of soft-tissue defects of the hand in 25 patients. Flap size varied from 3.5 × 2.0 cm to 24.0 × 4.0 cm, with a consistent thickness of approximately 3 mm. RESULTS: (1) There were 7 ± 2.0 ulnar artery perforators. The average external diameter was 0.6 ± 0.2 mm. Each perforator supplied an average area of 26 ± 7.0 cm(2). Extensive anastomoses were found between the ulnar artery perforators and multiple adjacent source arteries. (2) All flaps survived. The clinical results were satisfactory after 10.2 ± 5.3 months of follow-up. The flaps were considered cosmetically acceptable by both patients and doctors. CONCLUSIONS: The main advantage of the proximal ulnar artery perforator flap is that it is a thin flap that is ideal for upper extremity reconstruction, either as proximally or distally based local perforator flap or as a free flap. The donor site is excellent, and the vascular anatomy is very consistent.